From Concept to Practice - Abd Razak; Saifuddin A. Rasyid; Rahmad Syah Putra; M. Khatami; Asyraf Muntazhar; Nasrul Habibi; Hayatun Nufus (Esensia: Jurnal Ilmu-Ilmu Ushuluddin, 2025)
This study examines the implementation of religious moderation (MB) in State Islamic Higher Education Institutions (PTKIN) in Aceh, Indonesia, within the context of national policy and local religious dynamics. Drawing on empirical data and institutional analysis, the research identifies key structural and cultural factors that influence the effectiveness of the religious moderation agenda. While the concept of moderation is theologically compatible with Acehnese Islamic traditions, its institutionalization faces challenges, including the absence of integration into strategic planning, limited financial support, and varied cultural reception among academic communities. UIN Ar-Raniry Banda Aceh emerges as a leading institution with a more structured and sustained implementation, demonstrating the importance of leadership commitment and resource allocation. In contrast, other PTKINs show fragmented and ad hoc efforts due to organizational and financial constraints. The study finds that localized approaches—anchored in contextual theology, local customs, and credible religious authority—are more effective in fostering acceptance and operationalization of moderation values. These findings suggest that successful implementation of religious moderation in higher education requires a combination of policy integration, institutional support, and cultural engagement. The study contributes to the broader discourse on how national religious policies can be adapted to diverse local contexts without compromising institutional autonomy or theological integrity.